2011
DOI: 10.1111/j.1349-7006.2011.01918.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic enhancement and clinical effect by type‐I interferon of anti‐apoptotic protein, survivin‐derived peptide vaccine, in advanced colorectal cancer patients

Abstract: We previously identified a human leukocyte antigen (HLA)-A24-restricted antigenic peptide, survivin-2B80-88, recognized by CD8+ cytotoxic T lymphocytes (CTL). Subsequently, we attempted clinical trials with this epitope peptide alone for some malignancies, resulting in clinical and immunological responses, although their potential was not strong enough for routine clinical use as a cancer vaccine. In the current study, to assess whether immunogenicity of the survivin-2B80-88 peptide could be enhanced with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 28 publications
1
57
0
Order By: Relevance
“…However, a clinical efficacy study with p53-SLP in combination with IFN-α remains to be performed. Similar to this finding, combined treatment with IFN-α resulted in clinical improvement and enhanced immunological responses in CRC patients undergoing peptide vaccination with survivin-2B80-88 peptide [17,18]. Since helper T cells are known to play crucial roles in the efficient induction of CTL responses, cancer vaccines, which consist of both class I-restricted CTL epitopes recognized by CD8 + T cells and HLA class II-restricted helper epitopes recognized by CD4 + T cells, might be promising [27].…”
Section: Peptide Vaccinessupporting
confidence: 80%
See 1 more Smart Citation
“…However, a clinical efficacy study with p53-SLP in combination with IFN-α remains to be performed. Similar to this finding, combined treatment with IFN-α resulted in clinical improvement and enhanced immunological responses in CRC patients undergoing peptide vaccination with survivin-2B80-88 peptide [17,18]. Since helper T cells are known to play crucial roles in the efficient induction of CTL responses, cancer vaccines, which consist of both class I-restricted CTL epitopes recognized by CD8 + T cells and HLA class II-restricted helper epitopes recognized by CD4 + T cells, might be promising [27].…”
Section: Peptide Vaccinessupporting
confidence: 80%
“…For treatment of CRC patients, short or long peptides derived from various TAAs, including carcinoembryonic antigen (CEA) [11], heat shock protein (HSP) [12], melanoma antigen family (MAGE)-A4 [13], p53 [14,15], squamous cell carcinoma antigen recognized by T cells (SART) 3 [16], Survivin-2B [17,18] and many other antigens [19,20], have been used for vaccination. Since vaccination with a single short peptide showed only limited clinical responses, several modified approaches, such as long peptide [14,15], hybrid peptide [13], and multi-peptide cocktail vaccines [21], have been tried.…”
Section: Peptide Vaccinesmentioning
confidence: 99%
“…82 Furthermore, incomplete Freund's adjuvant and type-I interferon (IFNα) are two adjuvants that can enhance survivin-specific antitumor immunity. 77,83,84 In summary, we identified survivin as an independent prognostic factor for poor outcome in activated B cell-like diffuse large B-cell lymphoma patients treated with R-CHOP. Our findings suggest that survivin affects the survival of activated B celllike diffuse large B-cell lymphoma patients by influencing the mitosis and/or proliferation of tumor cells and is a promising therapeutic target in diffuse large B-cell lymphoma and its subgroup patients.…”
Section: Discussionmentioning
confidence: 83%
“…There are several reports showing that survivin autoantibodies have been detected in some cancer patients, such as lung, breast and colorectal cancer patients (AlJoudi et al, 2006;Karanikas, 2009;Chen et al, 2010), as well antibodies to MUC1 (Hirasawa et al, 2000;Tang et al, 2010). Moreover, several studies have revealed that vaccines targeting survivin or MUC1 VNTR can elicit both specific humoral and cellular immune responses both in pre-clinical and clinical trials (Tang et al, 2008;Yuan et al, 2010;Ishizaki et al, 2011;Kameshima et al, 2011), indicating that they are potent cancer vaccine targets. However, the correlations between auto-antibodies to survivin and MUC1 VNTR remain unknown.…”
Section: Introductionmentioning
confidence: 99%